Residential Segregation and Immigrants' Satisfaction with the Neighborhood in Germany - Verena Dill; Uwe Jirjahn; Georgi Tsertsvadze (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2011)
Using data from the German Socio-Economic Panel, this study examines the relationship between immigrant residential segregation and immigrants' satisfaction with the neighborhood. The estimates show that immigrants living in segregated areas are less satisfied with the neighborhood. This is consistent with the hypothesis that housing discrimination rather than self-selection plays an important role in immigrant residential segregation. Our result holds true even when controlling for other influences such as household income and quality of the dwelling. It also holds true in fixed effects estimates that account for unobserved time-invariant influences.
Keywords: J15; J61; R23; R30; 330; Immigrant Residential Segregation; Housing Discrimination; Self-Segregation; Neighborhood Satisfaction